REFLECTION OF THE DESTINY OF THE NATION IN CHOLPAN'S SMALL PROSE WORKS - Sohiba Arzikulova (European Science Publishing, 2024)
This article highlights the reflection of the fate of the nation in Cholpon's small prose works, in particular, "Victim of Ignorance", "Doctor Muhammadiyor", "Baker Girl", "October Girl". It is emphasized that Cholpon's short stories were the basis for the creation of the novel "Night and Day". Cholpan's skill in showing the reasons for the events that made a radical change in the fate of the characters in the above-mentioned works is revealed.
Keywords: ignorance, story, education, ignorance, ignorance, people's disease, existing conditions, people's life.